Double [3 + 2]-dimerisation cascade synthesis of bis(triazolyl)bisphosphanes, a new scaffold for bidentate bisphosphanes1. Issue 28 (28th July 2015) - Laborde, Coralie; Wei, Muh-Mei; van der Lee, Arie; Deydier, Eric; Daran, Jean-Claude; Volle, Jean-Noël; Poli, Rinaldo; Pirat, Jean-Luc; Manoury, Eric; Virieux, David
<x xml:space="preserve">Abstract</x> Highly convergent synthesis of bis(triazolylphosphane oxides) by a tandem copper-mediated Huisgen reaction–oxidative coupling.